Gymnasium Teachers’ Training - Dukynaite, Rita (Acta Paedagogica Vilnensia, 2000)
The reform of structure and content of education in Lithuania is being carried out. One of its components is quality improvement of secondary schools in pursuit of transforming best secondary schools into gymnasiums where common subjects will be taught at higher level. The article analyses the experience of secondary schools in Lithuania in the period of transition into the gymnasium status.